Biopesticides And Biofertigation Practice to Overcome Land Fertility and Plants Cultivation Problems in Magetan District - Indriya Radiyanto; Siswanto Siswanto; Indra Tjahaya Amir (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2018)
Magetan Regency is one of the leading fruit production centers (Pamelo Oranges) and vegetables in East Java. Production of Pamelo orange as a superior product of Magetan regency, during the last 10 years tends to decrease both in terms of quantity and quality. This is as a result of fruit fly pest attack is quite massive and viral; as well as vegetable crops that still depends on pesticide and chemical fertilizers. Quantity and quality of fruit and vegetable products are still not optimal because: 1). There are still pests and diseases that can not be controlled in an environmentally friendly manner, 2) The cultivation of pamelo and vegetable plants in Magetan regency has not been fully applied organic fertilizer intake, 3). Gardening irrigation technology still relies on rain water and semi-technical irrigation. The objective of the action research through Community Partnership Program (CPP) is to provide a touch of science and technology that is expected to accelerate the creative economic activities of the community by providing skills training based on organic materials including: 1. The utilization of yard land by planting vegetables; 2. The production soil enhancer; 3. Production of urine-based biopesticide ; 4. Simple book keeping practice in small-medium scale agriculture, and 5. Production of Pamelo orange-based food. The methods used in facilitating the improvement of skills of farmers and dairy farmers joined in micro small and medium enterprises including lecture, field practice and mentoring. The result of activities is expected to be able to: a). improve farmers skills in good plant care through integrated pest and disease control and organic based fertilization through fertigation. b). Make environmentally friendly fertilizers and pesticides independently. c). Increasing the production and quality of agricultural products. d). Innovative organic biofertilizers products.